Food product quality, environmental and personal characteristics affecting consumer perception toward food - Rai, Sampurna; Wai, Phu Pwint; Koirala, Pankaj; Bromage, Sabri; Nirmal, Nilesh Prakash; Pandiselvam, Ravi; Nor-Khaizura, Mahmud Ab Rashid; Mehta, Naresh Kumar (Frontiers in Sustainable Food Systems, 2023)
Food industries are developing new processing technologies, resulting in the emergence of new product categories, including ready-to-eat meals, functional foods and beverages, and plantbased foods, etc. Rapid globalization, changes in lifestyle, consumer awareness, and perception towards food drive further technical advancements. However, consumer perception remains the prime factor for food marketing and technological development. Consumer perception is a trifecta of sensory properties, personal and environmental factors. Sensory and personal factors include consumer age, attitude, health condition, nutrition awareness, and religion which directly influence consumer choice. Whereas environmental factors consist of regional variation in the food process, national economic status, and consumer purchasing power. All these factors affect consumers' decisions to accept or reject foods. Additionally, consumers are more willing to taste innovative food products that assure the safety and quality of the product.